2021
DOI: 10.3390/microorganisms9051037
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Diet and Sex on the Gut Microbiota of Lean and Obese JCR:LA-cp Rats

Abstract: There is an increased interest in the gut microbiota as it relates to health and obesity. The impact of diet and sex on the gut microbiota in conjunction with obesity also demands extensive systemic investigation. Thus, the influence of sex, diet, and flaxseed supplementation on the gut microbiota was examined in the JCR:LA-cp rat model of genetic obesity. Male and female obese rats were randomized into four groups (n = 8) to receive, for 12 weeks, either (a) control diet (Con), (b) control diet supplemented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Overall, the alpha diversity of the HW group was higher than that of the LW group, which was consistent with the research results on weaned piglets (Han et al, 2017). However, another study on rats found that the alpha diversity of obese rats was lower than that of lean rats (Resch et al, 2021). We speculate that this situation is due to possible differences in the composition and development of the GM between species.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, the alpha diversity of the HW group was higher than that of the LW group, which was consistent with the research results on weaned piglets (Han et al, 2017). However, another study on rats found that the alpha diversity of obese rats was lower than that of lean rats (Resch et al, 2021). We speculate that this situation is due to possible differences in the composition and development of the GM between species.…”
Section: Discussionsupporting
confidence: 90%
“…were minor components. Hence, it may be speculated that the genera present here were able to perform SDG degradation [ 48 ]. However, SECO was also not completely degraded to ED and EL in this study.…”
Section: Discussionmentioning
confidence: 99%
“…An increased abundance of Lactobacillus and Ruminococcus were also associated with lower HFF consumption. The abundances of these bacteria are disturbed in animal models fed a high-fat diet ( Daniel et al, 2014 ; Resch et al, 2021 ), which indicates that these taxa may not grow well in the gut in the presence of high-fat foods. Hence, in this study, lower reporting of HFF dietary behaviors among children perhaps favors the growth of these bacteria.…”
Section: Discussionmentioning
confidence: 99%